The MISLI-Drive, a modular sterilizable robotic driver for steerable laparoscopic instruments - Lenssen, Tomas; Bîrjac, Radu; Dankelman, Jenny; Horeman, Tim (Frontiers in Robotics and AI, 2023)
Introduction: Based on the success of the former 'Shaft-Actuated, Tip-Articulated' SATA-Drive, a prototype robotic instrument driver for modular, steerable, laparoscopic instruments, a new driver is designed and tested to improve previously lacking features concerning cleanability, instrument adaptation, practical application and control. The design of the driver engages these issues with a modular design aimed at re-use of both the instrument and the driver, for which a set of design requirements are established.Methods: A new modular design has been developed to improve cleanability through separation of the electro-motors and the instrument mechanism which clutches the instrument. Contamination of the driver's robotic side is prevented though a combination of a drape and a sterilizable barrier interface, while the instrument side is made sterilizable. A novel instrument clutching mechanism enables quick-release features, while a motor-axis latching mechanism enables plug-and-play assembly. Embedded sensors allow precise and fast control. A user-experiment was conducted on instrument exchange and assembly time, while mechanical and electrical tests were conducted on the driver's responsiveness.Results: The driver has proven its ability to control the instrument, after which it can be disassembled for cleaning and inspection. The driver is designed for re-use through disassembled sterilization where all possibly contaminated surfaces are exposable for cleaning and inspection.The new standardized instrument clutches allow easy instrument (dis-)assembly. Instrument exchange is possible in two methods, the fastest of which is a median of 11 (6.3-14.6) seconds. The driver's instrument mechanism is separated in a median of 3.7 (1.8-8.1) seconds. After assembly, the driver is operational in less than 2 seconds. Discussion: Instrument exchange times are similar to the semi-reusable Da Vinci systems, yet the MISLI-Drive is designed for sterilization, inspection and continual re-use. The modular build of the driver also allows easier parts replacement during maintenance, and requires minimal adaptation to different future scenarios, which is expected to reduce the overall cost of use. General re-use of medical devices, as well as the ability to selectively purchase, combined with a focus on low production costs, should reduce the overall cost of robotic surgery, making it more accessible.